Respuesta :

Let y=x+6 be equation 1...
Replace equation 1 in equation 2
X+6 =-2x-3
X+2x = -3 -6
3x = -9
X = -3
Substitution is when you plug in one value of a variable into an equation. In this case the value of y is given. Plug (x+ 6) into the equation: y=-2x - 3

You should get something like this:
x + 6 = -2x - 3
From there you can add 2x to both sides, and subtract 6 from both sides to get this:
3x = -9
Divide both sides by 3
x = -3
Now that you have the value for x, plug -3 into the equation y = x + 6

y = -3 + 6 = 3

The final answer is D) {-3,3}

*btw in case you didn't know this, the first number in an ordered pair is "x" while the second is "y"
ACCESS MORE